Use of Oral Anticoagulant for Prevention of Embolic Stroke and Systemic Embolism in Atrial Fibrillation - Jirapattrathamrong, Somboon (Vajira Medical Journal : Journal of Urban Medicine, 2018)
Oral anticoagulant has the important role for prevention of embolic stroke and systemic embolism in patient with atrial fibrillation. Warfarin has been widely used as standard prophylactic medication for a long time. Currently, novel oral anticoagulants (NOACs) could demonstrate the evidence of good efficacy for prevention of embolic stroke with reduction of bleeding complication related with oral anticoagulant in atrial fibrillation